MEMBANGUN BUDAYA KERJA SYARIAH DALAM UPAYA MENINGKATKAN KUALITAS KINERJA DOSEN (PENELITIAN DI UNIVERSITAS DJUANDA BOGOR) - Addinul Ikhsan; Maya Panorama; KMS Badaruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
The objective of this research was to disclosure comprehensive the Culture Building of Sharia at Djuanda University (UNIDA) Bogor. It was qualitative research by using case study at Universitas Djuanda Bogor Jawa Barat Indonesia in 2014. The data were collected through participant observation using interview, observation, document and recordings. The data analysis and interpretation indicates that (1) Tawheed had been made the main cultural source, guide and direction underlying throughout the process and comprehensive as well as holistic education components. (2) The process of developing tawheed-based work culture tended through the process of system synthesis in the university and the system in Ma'had (Rusunawa). (3) The working environment was very conductive to the establishment of sharia culture and a shift in the religious campus climate, policies, regulations, and leadership support. (4) syariah work culture positive impact on improving the quality of institution performance in implementing the Tri Dharma University, both academic, research and community service .